Declining memberships and Australia's political party registration test: Legal doubts and democratic principles. (June 2022) - Head, Michael
In recent decades, membership of established parties in parliamentary democracies such as Australia has been in marked decline. This has been accompanied by the regulation of political parties, featuring membership tests for the registration of non-parliamentary parties. This article raises questions about both the legality and democratic credentials of the 'membership testing process' applied by the Australian Electoral Commission (AEC).